Queen Sugar. The complete first season [videorecording (DVD)] - Wesley, Rutina; Gardner, Dawn-Lyen; Siriboe, Kofi, 1994-; Baszile, Natalie (Warner Bros. Home Entertainment, 2017)
Produced by Oprah Winfrey, award winning filmmaker Ava DuVernay, and Melissa Carter. After a family tragedy forces them back together, the Bordelons must navigate the triumphs and struggles of their complicated lives in order to run an ailing sugarcane farm in the Deep South.